Acting as Policy Entrepreneurs During COVID-19: The Case of Serbian Think Tanks - Djordjevic,Irena (2020)
Abstract The starting point of this paper is John Kingdon’s (1984) Multiple Streams approach used to analyze whether think tanks can be acknowledged as policy entrepreneurs during COVID-19 crisis. For such purpose, the case of Serbian think tanks is examined, analyzing problems they raised, policy alternatives they proposed along with strategies they applied. Moreover, by comparing issues brought by think tanks and Governmental policy, it is assessed to what extent think tanks proposals match with the ones the Government introduced. The findings show that the selected think tanks applied diverse strategies in addressing problems, which were in majority cases accompanied with specific proposals on how to resolve them. In addition to focusing on issues that are in line with their area of work and referring to their pet proposal, think tanks as well raised some new problems, which were not on their agenda before. Finally, more than half of the problems addressed in the Government program were also recognized as important by think tanks. Therefore, it may be concluded that think tanks played the role of policy entrepreneurs during COVID-19 crisis, but in order to assess whether they were the ones that brought such ideas to policy makers, further analysis is required.